Motivational orientations of teachers in the National Professional Qualification for Headship (NPQH) programme - Joned, Rusinah; Hong, Lee Leh (Universiti Putra Malaysia Press, 2006)
The aims of the study were to identify the motivational orientations of teachers as adult learners participating in the NPQH programme, to ascertain the relationship between academic attainment of teachers and the motivational orientations, and to determine whether the rank importance of motivational orientations were different within the different type of academic attainment of the teachers. The instrument used was 42 items statement of modified Educational Participation Scale (Boshier 1982). A total of 215 valid responses were accepted and analysed. The highest ranked motivational orientations were "professional advancement", followed by "educational preparation" and "cognitive interest". A negative and low but significant relationship was found between the academic attainment of teachers with "Educational Preparation" and "Family Togetherness". However further analysis showed that there were significant differences between "Communication Improvement", "Educational Preparation" and "Family Togetherness" with the academic attainments of teachers. It can be concluded that the teachers with degrees must have seen the importance of educational preparation for further education, enhancing family togetherness and to improve their communication skills.